Clays and Clay Minerals, Vol. 57, No. 3, 290–301, 2009. - Du, Chunfang; Yang, Huaming (My University, 2009)
Synthetic siliceous mesoporous materials are of great value in many different applications, including nanotechnology, biotechnology, information technology, and medical fields, but historically the resource materials used in their synthesis have been expensive. Recent efforts have focused on indirect synthesis methods which utilize less expensive silicate minerals as a resource material. The purpose of the present study was to investigate talc, a natural silicate mineral, as one such resource. It was used as raw material to prepare two advanced materials: porous silica (PS) and ordered mesoporous silica (MCM-41). The PS, with a specific surface area of 260 m2/g and bimodal pore-size distribution of 1.2 nm and 3.7 nm, was prepared by grinding and subsequent acid leaching. The MCM-41, with a large surface area of 974 m2/g and a narrow pore-size distribution of 2.8 nm, was obtained using a surfactant, cetyltrimethylammonium bromide (CTAB), by hydrothermal treatment using the as-prepared PS as a source of Si. The two resultant materials were characterized by small angle X-ray diffraction (SAXRD) and wide-angle X-ray diffraction (WAXRD), high-resolution transmission electron microscopy (HRTEM), solid-state magic-angle-spinning nuclear magnetic resonance (MAS NMR), Fourier transform infrared spectroscopy (FTIR), and N2 adsorption-desorption measurements. Based on these measurements, possible processes of transformation of PS from talc, upon acid treatment, and the formation of MCM-41 were investigated systemically. Acid leaching induced the transformation of a rigid layered structure to a nearly amorphous one, with micropores formed by a residual layered structure and mesopores formed from a condensed framework. The MCM-41 was a mixture of silanol groups (Si(SiO)3(OH)) and a condensed Q4 framework structure (Si(SiO)4), with a small amount of remaining Q3 layered structure (Si(SiO)3OMg). The increased Q4/Q3 value confirmed greater polymerization of MCM-41 than of PS. At the low CTAB concentration used (2 wt.%), the highly charged silicate species controlled the surfactant geometry. Charge-density matching, together with the degree of polymerization of the silicates, determined the resultant mesophase.
Simple Synthesis And Characterization Of Nanoporous Materials From Talc
gsccm57302-du.pdf: 495KB
Keywords: Periodicals; Geology; Acid Leaching; Grinding; Hydrothermal Treatment; Mesoporous Silica; Nanoporous Silica; Silicate Minerals; Talc.